2020
DOI: 10.7150/jca.44847
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pre-treatment Model Predicting Risk of Developing Refractoriness to Transarterial Chemoembolization in Unresectable Hepatocellular Carcinoma

Abstract: Background and aim: Refractoriness to transarterial chemoembolization is common during the therapeutic process of hepatocellular carcinoma, which is an intractable issue and may compromise the prognosis. We aim to establish a pre-treatment model to identify patients with high risks of refractoriness. Methods: From 2010 to 2016, 824 treatment-naive patients who had initially underwent at least two sessions of transarterial chemoembolization in Zhongshan Hospital, Fudan University were retrospectively enrolled. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Increases in either tumor size or number lead to increased |tumor burdens that markedly influence liver cancer treatment outcomes (20,(27)(28)(29). Hu et al retrospectively analyzed the association between TACE refractoriness and various biomarkers; they proposed that the main risk factors for refractory TACE include AFP, some liver function indicators and tumor imaging findings (30). Taken together, these previous results are consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Increases in either tumor size or number lead to increased |tumor burdens that markedly influence liver cancer treatment outcomes (20,(27)(28)(29). Hu et al retrospectively analyzed the association between TACE refractoriness and various biomarkers; they proposed that the main risk factors for refractory TACE include AFP, some liver function indicators and tumor imaging findings (30). Taken together, these previous results are consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, appropriate judgement of TACE refractoriness is crucial. Several previous studies have reported predictive factors of TACE refractoriness 8 , 9 , however, the potential prediction of early TACE refractoriness have not been identified.…”
Section: Introductionmentioning
confidence: 97%
“…According to JSH-LGSGJ 2014 criteria, the incidence of TACE failure/refractoriness ranges from 37.0% to 49.3%. 13,14 Nevertheless, by emphasizing retrospective studies and consensus rather than high-level evidence, these definitions and subsequent treatment recommendations for TACE failure/refractoriness remain somewhat ambiguous and controversial. In addition, the epidemiological difference in research between Japan/Western countries and China reveals discrepancies in the extent of disease burden, whereby a relatively higher burden of HCC is reported in China.…”
Section: Introductionmentioning
confidence: 99%
“…According to JSH-LGSGJ 2014 criteria, the incidence of TACE failure/refractoriness ranges from 37.0% to 49.3%. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%